2020
DOI: 10.1108/ijssp-11-2019-0237
|View full text |Cite
|
Sign up to set email alerts
|

Journey from passion to satisfaction: roles of belongingness and psychological empowerment

Abstract: PurposeThe present research work is intended to investigate the work passion and job satisfaction relationship of social workers in Delhi/NCR and examine the influence of belongingness and psychological empowerment on the association. The study has used self-determination theory to support the relationship.Design/methodology/approachThe study used the standardized instruments to assess the relationship. Statistical tools such as SEM, convergent and discriminant validity, reliability, and moderated regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 71 publications
(91 reference statements)
1
30
0
1
Order By: Relevance
“…The discipline of HRD has supported the psychological need to belong (Maslow, 1970) as evidenced in many employee work concepts. Pathak and Srivastava (2020) reported that employees that have a greater sense of belonging at work experienced greater job satisfaction. Meyer, Stanley, Herscovitch, and Topolnytsky (2002) described affective commitment as an individual's feeling of belonging to an organization.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…The discipline of HRD has supported the psychological need to belong (Maslow, 1970) as evidenced in many employee work concepts. Pathak and Srivastava (2020) reported that employees that have a greater sense of belonging at work experienced greater job satisfaction. Meyer, Stanley, Herscovitch, and Topolnytsky (2002) described affective commitment as an individual's feeling of belonging to an organization.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Moving further employees with psychological empowerment have shown a strong willingness to complete work (Pathak and Srivastava, 2020;Salehi et al, 2020). Therefore, and backed up by existing research conducted by Grant et al (2007), Pathak and Srivastava (2020); Spreitzer (2008), Van De Voorde et al (2012) following hypotheses are proposed: H1. Psychological well-being has a positive influence on employee work engagement.…”
Section: Literature Review 21 Psychological Well-being and Empowermentmentioning
confidence: 99%
“…The impact of psychological factors is prominent in determining sustainable employability (van Dam et al, 2017). Nevertheless, psychological factors such as the psychological wellbeing of employees and psychological empowerment have shown a positive impact on employee behavior (Kundi et al, 2021;Pathak and Srivastava, 2020). The term psychological well-being denotes employee subjective experiences and functions that reflect one's personal growth and life satisfaction (Guest, 2017).…”
Section: Literature Review 21 Psychological Well-being and Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no studies that I know of have examined diversity climate as either an antecedent of workplace belongingness or the predictability of tacit knowledge sharing by both diversity climate and workplace belongingness. Rather, most studies on workplace belongingness as an antecedent has focused on well-being-related outcomes, such as depression (Cockshaw and Shochet, 2010;Cockshaw et al, 2014), professional quality of life (Somoray et al, 2017), job satisfaction and work engagement (Gatt and Jiang, 2020;Pathak and Srivastava, 2020) among others.…”
Section: Introductionmentioning
confidence: 99%